2020
DOI: 10.1042/bsr20192645
|View full text |Cite
|
Sign up to set email alerts
|

MiR-203a-3p regulates TGF-β1-induced epithelial–mesenchymal transition (EMT) in asthma by regulating Smad3 pathway through SIX1

Abstract: Asthma is a common chronic airway disease with increasing prevalence. MicroRNAs act as vital regulators in cell progressions and have been identified to play crucial roles in asthma. The objective of the present study is to clarify the molecular mechanism of miR-203a-3p in the development of asthma. The expression of miR-203a-3p and Sine oculis homeobox homolog 1 (SIX1) were detected by quantitative real-time polymerase chain reaction (qRT-PCR). The protein levels of SIX1, fibronectin, E-cadherin, vimentin, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It was also reported that miRNAs involved in regulating the proliferation, promotion, invasion and metastasis of tumor cells (9). Furthermore, miRNAs are somehow involved in Epithelialmesenchymal Transition (EMT), which is a significant indicator of the tumor metastatic process (10). Although the importance of miRNAs in tumor progression has been explored extensively, the pathological relevance and significance of miRNAs in colon cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that miRNAs involved in regulating the proliferation, promotion, invasion and metastasis of tumor cells (9). Furthermore, miRNAs are somehow involved in Epithelialmesenchymal Transition (EMT), which is a significant indicator of the tumor metastatic process (10). Although the importance of miRNAs in tumor progression has been explored extensively, the pathological relevance and significance of miRNAs in colon cancer remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…133,134 Orosomucoid-like 3 (ORMDL3), was shown to play an important role in regulating epithelial barrier function in allergic asthma, [135][136][137] rhinovirus infection 138,139 and by inducing the p-ERK/MMP-9 pathway to promote pathological airway remodeling in patients with asthma. 140 SMAD3 is an essential signal transducer in TGF-β signaling, which is elevated in airway epithelial cells of some asthmatics 141,142 and is involved in the response of bronchial epithelial cells to viral infection. 143,144 Deletion of P2Y13 in human airway epithelial cells and in a mouse model protects against asthma exacerbations.…”
Section: Genetic and Epigenetic Changes In Bronchial Epitheliummentioning
confidence: 99%
“…50,51 Studies have shown that TGF-β1 can regulate the miR-203a-3p/SIX1 signaling pathway to regulate the Smad3 pathway and promote the occurrence of epithelial-mesenchymal transition in asthma. 52 In vivo and in vitro experiments have found that icariin can significantly inhibit the phosphorylation of cytokines such as Erk, JNK, and p38; inhibit the activation of Smad and MAPK signaling pathways; and reduce the EMT process induced by TGF-β1 to improve airway remodeling. 53 proteins and reactive oxygen species (ROS), and cell endoplasmic reticulum dysfunction, stimulating the unfolded protein response (UPR), aggravating endoplasmic reticulum stress, airway inflammation, and airway remodeling processes.…”
Section: Icariin Could Inhibit Airway Epithelial Cell-to-mesenchymal Transition (Emt)mentioning
confidence: 99%